Analisis Pengaruh Produksi Kopi, Luas Lahan dan Kurs Rupiah Terhadap Volume Ekspor Kopi Indonesia Periode Tahun 2010 – 2020 - Laura Elfina Karo Karo; Noni Rozaini (Universitas 17 Agustus 1945 Semarang, 2023)
The volume of coffee exported from Indonesia between 2010 and 2020 will be reviewed in this study along with the influence of the variables coffee production, land area and exchange rate. In this study the influence of independent factors on dependent factors was assessed using multiple linear regression analysis techniques. The results of the multiple linear regression analysis of this study revealed that Indonesia's coffee exports were negatively affected but not significantly by variables related to coffee production. Indonesian coffee exports were negatively and insignificantly affected by changes in land area. Conversely, the exchange rate (exchange rate) has a positive but also insignificant impact on the volume of coffee exported from Indonesia.